Bacteriological assessment on urinary tract infection in preterm premature rupture of the membranes and preterm labour related to fetomaternal outcomes - Bargaje, Ganesh M.; Hussain, Roshan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Urinary tract infection (UTI) is a health hazards risk during pregnancy of mothers, which leads to preterm premature rupture of the membranes (PPROM) following preterm labour (PTL). The objective was to investigate the most common bacteria causing UTI in cases presenting with PPROM following PTL and also their sensitivity profile to antibiotics and fetomaternal outcome in such cases at tertiary care hospital, Central India. Methods: This research was conducted a hospital-based prospective and observational study among 60 pregnant women for the period of 01 July 2020 to 30 June 2021 in the tertiary care hospital at Bhilai, Chhattisgarh. Also studied urine for culture and sensitivity test for antibiotics related to fetomaternal outcomes. Results: Among the marker of infection of total studied patients, a maximum for UCS positive (21.7%) and WBC count >15000 cumm (15.0%) while minimum for CRP (10.0%). Among the various microorganisms isolated in urine culture of participants, a higher value was observed on E. coli (11.67%) followed by Klebsiella sp. and Proteus sp. (3.33%) while lower value was observed for Pseudomonas sp. and CoNS (1.67%) among total studied patients. The association between urine culture and maternal complications, type of delivery, did not show significant association. No significant association was observed between urine culture and different parameters of neonatal complications and neonatal death. Only two deaths of babies were recorded. Conclusions: UTI is significant causative factors of PTL and PPROM. It is always suggested to screen and monitor the antenatal mothers for the presence of asymptomatic or symptomatic UTI.